New England Puritans: The Grandparents of Modern Protestant Missions - Carpenter, John B. (Missiology, 2002)
New England Puritanism was decisive in preparing for the “Great Century of Missions.” Reaching the Native Americans was a leading rationale for the Puritans crossing the Atlantic in the first place. John Eliot established precedents that were looked to as models of missionary practice. David Brainerd joined Eliot as a model missionary, mostly through the writings of Jonathan Edwards, the last great Puritan. To that, Edwards added his emphasis on prayer and his theological struggles for an evangelistically minded Calvinism. His writings were key in teaching English Particular Baptists, among others, that God used means “for the conversion of the heathen.”